(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The present study aims to determine and assess the effects of implementing TQM principles on enhancing sustainable manufacturing, encompassing three dimensions of sustainable manufacturing and seven key aspects of TQM. The research question that emerged was whether it was crucial to construct and test a model that combined these two principles of the modern industrial workplace. The Kufa Cement Factory was selected as the study site, with a research population of 144 workers. We sent out 120 questionnaires, and 116 were returned with the necessary information to be utilized. The study employed descriptive, analytical, and quantitative methods, with SEM (AMOS V.26) serving as the primary statistical tool, and reliability and descriptive analysis were conducted using SPSS V.26. The statistical results confirmed the strong and significant influence of TQM principles on sustainable manufacturing. However, there were shortages in the dimensions of process management implementation and information and analysis, as interest in the economic dimension was the least favorable. The most vital recommendation is to implement a comprehensive program of digital transformation to address issues with administrative and operational readiness, and to enhance long-term economic performance through data-driven improvements.